Direct Growth Inhibitory Effect of Platelet Activating Factor C-16 and Its Structural Analogs on Mycobacteria - Riaz, Muhammad S.; Kaur, Anuvinder; Shwayat, Suha N.; Behboudi, Shahriar; Kishore, Uday; Pathan, Ansar A. (Frontiers in Microbiology, 2018)
Mycobacterium tuberculosis (M.tb), the causative agent of tuberculosis, is one of the leading causes of human deaths due to a single infectious agent. M.tb infection of the host initiates a local inflammatory response, resulting in the production of a range of inflammatory factors at the site of infection. These inflammatory factors may come in direct contact with M.tb and immune cells to activate different signalling pathways. One such factor produced in excess during inflammation is a phospholipid compound, Platelet Activating Factor C-16 (PAF C-16). In this study, PAF C-16 was shown to have a direct inhibitory effect on the growth of Mycobacterium bovis BCG (M.bovis BCG) and Mycobacterium smegmatis (M.smegmatis) in a dose and time-dependent manner. Use of a range of PAF C-16 structural analogues, including the precursor form Lyso-PAF, revealed that small modifications in the structure of PAF C-16 did not alter its mycobacterial growth inhibitory properties. Subsequent experiments suggested that the attachment of aliphatic carbon tail via ether bond to the glycerol backbone of PAF C-16 was likely to play a vital role in its growth inhibition ability against mycobacteria. Fluorescence microscopy and flow cytometry using Propidium iodide (PI) indicated that PAF C-16 treatment had a damaging effect on the cell membrane of M.bovis BCG and M.smegmatis. Furthermore, the growth inhibitory effect of PAF C-16 was partially mitigated by treatment with membrane-stabilizing agents, α-tocopherol and Tween-80, which further suggests that the growth inhibitory effect of PAF C-16 was mediated through bacterial cell membrane damage.